Classroom Techniques Used In Reading Activities In English Classroom A Naturalistic Study At MTs Negeri Surakarta 2 In 2015/2016 Academic Year - Setyani, Umi Laila, Prof. Dr. Endang fauziati, M. Hum, Aryati Prasetyarini S. Pd, M. Pd (2016)
This study is carried out to describe classroom techniques used in reading activities in English classroom at MTs Negeri Surakarta 2. The aims of this research are: (1) to describe the kinds of classroom techniques used in reading activities, (2) the purpose of using each classroom techniques, (3) the teacher's roles, (4) the student's roles, (5) the instructional materials used by the English teachers at MTs Negeri Surakarta 2. The type of this research is descriptive qualitative research especially naturalistic study in analyzing the data. The methods of collecting data in this research are observation, interview and document. The techniques of analyzing data are data reduction, data display, and conclusion. Credibility of the data is triangulation. The finding of the study shows that there are some classroom techniques used by English teachers at MTs Negeri Surakarta 2 such as: reading aloud, question and answer technique, silent reading, skimming, and number heads. The teachers have roles as model, instructor, signs of trouble, source of knowledge, facilitator, evaluator, and manager. The students have role as monitor and evaluate their own progress, learners plan their own learning program, tutor for the other students, learners learn from the teacher, member a group and learn by interacting with other, and actively in learning. There are some materials used by English teachers, such as textbook, work book, dictionary, photocopy exercises, and power point on LCD. The conclusion of this research is that English teacher at MTs Negeri Surakarta 2 used various classroom techniques which can improve the students' ability in reading. Various techniques make the student interested in English teaching-learning process. It does not make the class monotonous. The students become more active and creative. Based on the result, apparently, classroom techniques in teaching reading used by the teacher have important role in the teaching-learning process.